Filhos da globalização: a vivência dos filhos de pais expatriados - Veneziano, Polyana de Souza (2011)
The expatriation is a deep experience that mobilizes a huge amount of changes in the lives of individuals, it is a period of gains and losses, pleasure and displeasure. The main target of this job was to understand the experience of children that followed their parents in international assignments, in order to identify aspects considered by them as positive and negative and the impacts in their lives today. For this purpose, it was used life history of four young adults who lived through this experience during their childhood or adolescence, that means, retrospective memories of this stage. This study reveals that children can cope with this transition without suffering many impacts on their development. On the other hand, teenagers may face more difficulties, once they experience a transition of their own stage in the life cycle and also have to deal with another wave of transformations generated by expatriation . We conclude that the family, school and new bonds built in the host country were determining factors for success or failure of the acculturation process. In general, all these experiences were satisfactory and generated benefits for the current life of these individuals. The results may support mentoring programs and family preparedness